2022
DOI: 10.3390/fractalfract6040184
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of the Fractional-Order Mathematical Model Underlying Immune-Chemotherapeutic Treatment for Breast Cancer Using the Neural Networks

Abstract: The aim of this work is to design a stochastic framework to solve the fractional-order differential model based on the breast cancer progression during the immune-chemotherapeutic treatment phase, including certain control parameters such as anti-cancer medications, ketogenic diet and immune boosters. The developed model considers tumor density progression throughout chemotherapy treatment, as well as an immune response during normal cell–tumor cell interaction. This study’s subject seems to be to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The LVMBPNN can be used in future work to present numerical measures of the fractional order systems, lonngren-wave, fluid mechanics systems, omics studies, and data security models [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Resultsmentioning
confidence: 99%
“…The LVMBPNN can be used in future work to present numerical measures of the fractional order systems, lonngren-wave, fluid mechanics systems, omics studies, and data security models [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, stochastic solvers have been presented to solve the fractional dynamical models. Few of them are dynamical nonlinear susceptible infected and quarantine differential model [55], immune-chemotherapeutic treatment for breast cancer [56], nonlinear prey-predator system [57], SIDARTHE COVID-19 pandemic differential model [58], Bagley-Torvik mathematical model [59] and seventh order singular system [60]. It is found that the time FO derivatives have been applied to different conditions in various applications.…”
Section: Novel Stochastic Solvers Featuresmentioning
confidence: 99%
“…The data magnitudes are implemented 75% for training, 10% for certification and 15% for testing to solve the FO-HBV-DIS with the response of antibody immune. The stochastic numerical procedures have the competence and ability to solve the linear models as well as various stiff complex nonlinear systems [42][43][44][45][46][47][48][49][50]. These numerical performances of the integer order motivated the authors to present the numerical simulations of FO derivatives of nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%